DAMPER WINDING PHENOMENA OF SYNCHRONOUS GENERATOR UNDER UNBALANCED STEADY-STATE CONDITION: A CASE OF 500 KV EHV JAMALI SYSTEM - Sugiarto, Sugiarto; Hadi, Sasongko Pramono; Tumiran, Tumiran; Wijaya, F. Danang (ReTII, 2015)
The performance of three different damper winding configurations of a synchronous generator under unbalanced steady-state condition of the power system to which it is connected are investigated in this paper. This synchronous generator is a source of electrical energy generation system in the 500 kV EHV Jawa-Madura-Bali (or Jamali) System with untransposed transmission lines and many single-phase loads. Induced currents of damper windings under the unbalanced steady-state system conditions, when the synchronous generator is equipped with and without damper winding, are measured and analyzed. Active windows with this model are developed using Matlab’s Graphical User Interface (GUI) capability to examine the dynamic behavior of the machine after small perturbations, focusing on electromagnetically dynamic as affected by load unbalance. EDSA 2000 software is used to derive the generator’s terminal inputs through load-flow analysis on the grid. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> Theperformanceofthreedifferentdamperwindingconfigurationsofasynchronousgeneratorunderunbalanced steady-state conditionofthe power system towhichitis connected areinvestigatedinthis paper.This synchronous generator is asource ofelectricalenergy generationsystem inthe 500kVEHVJawa-Madura-Bali(or Jamali) System with untransposedtransmissionlines andmany single-phaseloads. Inducedcurrentsofdamperwindingsundertheunbalancedsteady-statesystemconditions,whenthesynchronous generatorisequippedwithandwithoutdamperwinding, aremeasuredand analyzed.Activewindowswiththismodelare developedusingMatlab’sGraphicalUserInterface(GUI)capabilitytoexaminethedynamicbehaviorofthemachine after smallperturbations,focusingonelectromagneticallydynamicas affectedbyloadunbalance. EDSA 2000softwareisusedto derive the generator’s terminalinputs throughload-flowanalysisonthegrid. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->